2017
DOI: 10.1186/s13256-017-1429-6
|View full text |Cite
|
Sign up to set email alerts
|

Beyond classic dermoscopic patterns of dermatofibromas: a prospective research study

Abstract: BackgroundThe usual stereotypical dermoscopic pattern associated with dermatofibromas is a pigment network and central white patch. However, this pattern may be difficult to diagnose in some variant cases. We aimed to describe dermoscopic patterns of dermatofibroma according to its histopathological subtypes, with special emphasis on new and rare dermoscopic features.MethodsThis prospective study, which was conducted between September 2015 and May 2016 in the Department of Dermatology, University Hospital Hass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 18 publications
2
65
0
3
Order By: Relevance
“…Atypical variants of DF, such as HDF (once progressed to aneurysmal DF [ADF]), are more likely to have high proliferative activity and recurring metastasis with metastasis noted as early as three months after first diagnosis [7,8]. In contrast, the median time-to-metastasis for localized melanoma is 28 months [9]. The hemosiderin deposits and dermal blood-filled cavities, characteristic of HDF, histopathologically resemble melanoma or vascular tumors [1,10].…”
Section: Discussionmentioning
confidence: 99%
“…Atypical variants of DF, such as HDF (once progressed to aneurysmal DF [ADF]), are more likely to have high proliferative activity and recurring metastasis with metastasis noted as early as three months after first diagnosis [7,8]. In contrast, the median time-to-metastasis for localized melanoma is 28 months [9]. The hemosiderin deposits and dermal blood-filled cavities, characteristic of HDF, histopathologically resemble melanoma or vascular tumors [1,10].…”
Section: Discussionmentioning
confidence: 99%
“…They typically occur as solitary lesions; however, multiple dermatofibromas can be associated with various conditions [5]. Several clinical and pathological variants of a dermatofibroma have been described (Table 1) [2–4, 611]. An atrophic dermatofibroma is a rare subtype of dermatofibroma [7–30].…”
Section: Discussionmentioning
confidence: 99%
“…Significant contributions to the atrophic dermatofibroma literature are summarized in Table 2 [79, 11–24]. In this article, we summarize the world literature on this subject.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The delicate light brown pigment network surrounding the tumor is related to the hyperpigmented rete ridges usually present at the edge of dermatofibromas. Kelati et al [8], reported a new dermoscopic description of this polymorphous tumor as a white ring around an ulceration associated with linear irregular vessels and dotted vessels. These findings were related to the histological presence of large and superficial bloodfilled spaces that may cause epidermal removal and ulceration surrounded by fibrosis.…”
Section: What's Your Diagnosis?mentioning
confidence: 99%